Noble hybrid composite coated low alloy steel for high temperature applications - Maleque, Md. Abdul; Bello, K. A. (2017)
A promising approach is introduced in this invention based on hybrid coating system where materials such as solid lubricant of surface activated hexagonal boron nitride (hBN) is deposited along with hard TiC material on the low alloy steel (LAS) substrate. This strategy was developed to provide low wear and friction properties of LAS especially at high temperature. A cheaper powder preplacement and tungsten inert gas (TIG) arc torch method was employed to synthesize TiC/Ni-P-hBN composite hybrid coating in the near-surface region of AISI 4340 low alloy steel (LAS) material. Melt pool characteristics of hybrid composite coatings showed better surface morphology whereby coating produces melt pool with no visible defects resulting in an effective integration between TiC and hBN. Wear scar of TiC/Ni-P-hBN coating showed mild abrasive wear with stable frictional control at high temperature. In order to meet the requirement of demanding high-temperature tribological applications, this new invention has developed and proved an effective composite coating based on the advanced lubrication concept of combining hard TiC and soft reinforcement phase of surface activated hexagonal boron nitride (Ni-P-hBN).